Multidimensional Strongly Deferred Invariant Convergence. (18th August 2021) - Savaş, Rabİa
Abstract: The primary purpose of this article is to introduce double deferred invariant statistical convergence and double strongly invariant convergence for double sequences. Additionally, some implications are examined.